Association between left ventricular perfusion defects and myocardial deformation indexes in heart transplantation recipients. Issue 10 (3rd July 2017) - D'Andrea, Antonello; De Rimini, Maria Luisa; America, Raffaella; Cirillo, Chiara; Riegler, Lucia; Limongelli, Giuseppe; D'Alto, Michele; Salerno, Gemma; Maiello, Ciro; Muto, Pietro; Russo, Maria Giovanna; Calabrò, Raffaele; et al.
Abstract : The aim of the study was to analyze possible correlations between strain echocardiography (STE) and PET myocardial perfusion in a population of heart transplantation (HTx) recipients showing preserved left ventricular (LV) ejection fraction. By STE, LV global longitudinal strain (LV GLS) was lower in HTx. PET showed no transient or chronic ischemia in 83 of 115 HTx (73%). Fixed perfusion defects were observed in 17% of HTx and reversible ischemia in 10%. Significant coronary stenosis was observed only in 10 cases. GLS was independently associated with age at HTx and fixed perfusion defects (HR 0.41; P <.001). Such relationships underline STE ability to early identify HTx pts with subclinical myocardial dysfunction during long‐term follow‐up.